Revisiting a Flag Salute Case: The Law of the State as Opposed to the Right of Minority - Nealega, Rosabella; Rosialda, Ailene; Caspe-Ogatis, Gerlie; Bautista, Ana Marie (Social Sciences and Development Review, 2023)
The state as an agent responsible to secure social order is oftentimes given high regard by its citizens based on the premise that it can also guarantee protection of rights through the formulation of laws that set legal boundaries in safeguarding the interests of the people. The state is the actual reality of an ethical idea according to some philosophers, like Hegel, because it is created with a noble purpose of upholding the common good of its subjects, the essence of which is to secure happiness and safety for all. Conflicts may, however, arise in occasions where individual rights run counter with the policies of the land. This is the focus of this study; on the one hand, an intriguing exposition on the exercise of religious freedom of a minority group, and on the other, its conflict with the legal policies promoting a conceived general welfare for the country.